2022
DOI: 10.1002/anie.202207988
|View full text |Cite
|
Sign up to set email alerts
|

Dual Nickel/Photoredox‐Catalyzed Site‐Selective Cross‐Coupling of 1,2‐Bis‐Boronic Esters Enabled by 1,2‐Boron Shifts

Abstract: Site‐selective transition‐metal‐catalyzed mono‐deboronative cross‐couplings of 1,2‐bis‐boronic esters are valuable methods for the synthesis of functionalized organoboron compounds. However, such cross‐couplings are limited to reaction of the sterically less hindered primary boronic ester. Herein, we report a nickel/photoredox‐catalyzed mono‐deboronative arylation of 1,2‐bis‐boronic esters that is selective for coupling of the more sterically hindered secondary/tertiary position. This is achieved by taking adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 106 publications
0
9
0
Order By: Relevance
“…In the same year, the authors also reported the arylation of 1,2-bis-boronate esters with (hetero)­aryl halides via dual nickel/photoredox catalysis, overcoming the limitations of the previous protocol regarding the use of only electron-deficient arylnitriles . The use of anionic diketonate-based ligands proved to be critical for the regioselectivity of the transformation in comparison to bipyridine ligands, and the study revealed the ligand TMHD was optimal, providing the product with >20:1 rr.…”
Section: 2-boron Shifts Of β-Borylated Radicals Generated From Bis-bo...mentioning
confidence: 99%
See 1 more Smart Citation
“…In the same year, the authors also reported the arylation of 1,2-bis-boronate esters with (hetero)­aryl halides via dual nickel/photoredox catalysis, overcoming the limitations of the previous protocol regarding the use of only electron-deficient arylnitriles . The use of anionic diketonate-based ligands proved to be critical for the regioselectivity of the transformation in comparison to bipyridine ligands, and the study revealed the ligand TMHD was optimal, providing the product with >20:1 rr.…”
Section: 2-boron Shifts Of β-Borylated Radicals Generated From Bis-bo...mentioning
confidence: 99%
“…In the same year, the authors also reported the arylation of 1,2-bis-boronate esters with (hetero)aryl halides via dual nickel/photoredox catalysis, overcoming the limitations of the previous protocol regarding the use of only electrondeficient arylnitriles. 62 The use of anionic diketonate-based ligands proved to be critical for the regioselectivity of the transformation in comparison to bipyridine ligands, and the study revealed the ligand TMHD was optimal, providing the product with >20:1 rr. The effects of the ligands on the regioselectivity are in accordance with findings reported in a study by Molander and co-workers, showing a difference regarding the mechanisms for the reductive elimination step, outer-sphere (for the diketonate ligands) and inner-sphere (for the Ni-bipyridyl system).…”
Section: Protocols In the Modification Of Bioactive Substratesmentioning
confidence: 99%
“…Interestingly, the procedure has been applied to cyclopentane and cyclohexane cis-1,2-bis(boronates), yielding trans-arylation products for both substrates, unlike the Suzuki−Miyaura cross-coupling that renders the cis-arylated diastereoisomers (Scheme 24b). In a later development of this group, 33 the generation of the secondary radical from 1,2-bis(boronates) can be merged with a dual nickel/photoredox-catalyzed cross-coupling, expanding the scope from (hetero)aryl nitriles to (hetero)aryl bromides (Scheme 24c). Remarkably, starting from vicinal bis-(boronates), this methodology allows for arylation of the more substituted boronic ester (secondary or tertiary) and it is complementary to arylation of the less hindered primary boronic ester by means of a Suzuki−Miyaura cross-coupling.…”
Section: Selective Homolytic Cleavage Of a C−b Bondmentioning
confidence: 99%
“…1a). However, despite the elegant strategies developed to selectively functionalize 1,2-bis-boronates, 11,12 the enantioselective desymmetrization of these species is still an unmet challenge (Fig. 1b).…”
Section: Introductionmentioning
confidence: 99%